Pengaruh Gaya Komunikasi dan Gaya Kepemimpinan dalam Membangun Loyalitas Karyawan - Ritonga, Zuriani; Maulana, Rizkha; Murniyanti, Sri; Zuhra, Fatimah; Sutoyo, Sutoyo (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The aim of this research is to analyze communication style and leadership style factors in building employee loyalty at Raja Mart in Bireuen Regency. This research approach is descriptive qualitative research. As informants are the owner/leader and several employees of Raja Mart, Bireuen. Data collection uses interview techniques or direct structured interviews. The data analysis technique uses a descriptive analysis model. The research results show that: 1) communication style has a significant influence on employee loyalty 2) leadership style has a significant influence on employee loyalty 3) employee loyalty is jointly influenced by the way leadership and communication are enforced.